2010
DOI: 10.1007/s11432-010-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microwave brightness temperature of lunar surface and inversion of regolith layer thickness: Primary results of Chang-E 1 multi-channel radiometer observation

Abstract: In China's first lunar exploration project, Chang-E 1 (CE-1), a multi-channel microwave radiometer was aboard the satellite, with the purpose of measuring microwave brightness temperature from lunar surface and surveying the global distribution of lunar regolith layer thickness. In this paper, the primary 621 tracks of swath data measured by Chang-E 1 microwave radiometer from November 2007 to February 2008 are collected and analyzed. Using nearest neighbor interpolation based on the sun incidence angle in obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Apollo in situ measurements showed that most of the lunar surface consists of a fine‐grained regolith layer that covers the underlying, highly fractured basement materials (i.e., megaregolith). The average thickness of the fine‐grained regolith layer is 4–5 m for the maria and 10–15 m for the highlands (Fa & Jin, ; Montopoli et al, ; Shkuratov & Bondarenko, ). The penetration depths of 19.35‐ and 37‐GHz microwaves are no more than 1 m on the Moon (Fang & Fa, ; Wang et al, ), which is smaller than the typical thickness of the regolith.…”
Section: Simulation Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Apollo in situ measurements showed that most of the lunar surface consists of a fine‐grained regolith layer that covers the underlying, highly fractured basement materials (i.e., megaregolith). The average thickness of the fine‐grained regolith layer is 4–5 m for the maria and 10–15 m for the highlands (Fa & Jin, ; Montopoli et al, ; Shkuratov & Bondarenko, ). The penetration depths of 19.35‐ and 37‐GHz microwaves are no more than 1 m on the Moon (Fang & Fa, ; Wang et al, ), which is smaller than the typical thickness of the regolith.…”
Section: Simulation Approachmentioning
confidence: 99%
“…Over the course of those missions, the Microwave RadioMeter (MRM) onboard both orbiters obtained repeat coverage of global microwave brightness temperature (T B ) at four frequencies (Fang & Fa, ; Zheng et al, ). Based on observed and modeled T B , a number of inversion schemes have been developed to investigate lunar regolith thickness (Fa & Jin, ; Zhou et al, ), He‐3 content (Fa & Jin, ), dielectric constant (Gong et al, ; Wang et al, ), and subsurface temperatures (Gong & Jin, ; Wei et al, ). However, these studies assumed a smooth spherical model for calculating lunar surface temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In polar region, CE-1 TB map shows some cold patches, where local temperature minima are independent of day and night due to absence of direct illumination in PSRs [13]. MRM data have also been utilized in inferring the properties of the upper few meters of lunar surface in low and middle latitudes; e.g., the thickness distribution of regolith was retrieved using the MRM data [25], the effective complex dielectric constant of lunar regolith as a function of the depth at different frequency channels [26], lunar (FeO + TiO 2 ) abundance [27], rock abundance, and others [28]. Also, people had studied basaltic volcanism of the Moon with MRM data [29].…”
Section: Introductionmentioning
confidence: 99%
“…In the existing emission models for lunar regolith [ Fa and Jin , , , ; Meng et al ., ; Wang et al ., ], many factors influencing the TBs are considered, such as the regolith layer thickness, the temperature profile, the lunar soil bulk density, and the dielectric permittivity profiles. Usually, the regolith is modeled to a layered medium with plane interfaces [ Fa and Jin , , , ; Meng et al ., ; Wang et al ., ]. Coherent or noncoherent radiative transfer models are used to calculate the TBs of the layered medium.…”
Section: Introductionmentioning
confidence: 99%
“…For roughness whose scale is assumed to be characterized by slowly varying undulations with a horizontal scale that is large compared to the wavelength, a statistical geometric optics (GO) approach is employed. To study the influence of the terrains on the microwave TBs shown by Jin and Fa [], the undulating surface is divided into discrete triangular meshes, whose dimensions are 10 m. Also, the surface of each mesh is regarded as a plane. The results show that in the regions of spatial resolutions of the multichannel microwave radiometer, the effects of the terrains on the emission can be neglected.…”
Section: Introductionmentioning
confidence: 99%